Evaluation and optimization of bridge deck waterproof bonding system using multi-objective grey target decision method. Issue 7 (2nd October 2020) - Qiu, Yanjun; An, Shaoke; Rahman, Ali; Ai, Changfa
Abstract : Surfacing of steel decks is one of the crucial issues which engineers are facing during construction of long-span steel bridges. This study aims to optimise the overall performance of the bridge deck waterproof bonding system. The waterproof bonding system used in this study consisted of two layers, a waterproof layer and a bonding layer. The role of the bonding is to ensure that the deck pavement and the steel panel can form a monolithic structure. The waterproof layer mainly prevents moisture from penetrating into the bridge deck. A series of laboratory experiments were conducted to evaluate the bonding performance of the waterproof adhesive system. Different types of waterproof adhesive systems were considered in the experimental design. Five performance indicators such as tensile strength, direct shear strength, skew shear strength, fatigue life, and project cost, were incorporated for evaluation. Then, the multi-objective grey target decision approach was employed as an optimised method to recommend a suitable waterproof adhesive system. Results showed that the temperature and performance indicators had a significant influence on the ranking of varying waterproof bonding system types. Findings of this research could provide the technical support for the future design of bridge deck waterproof adhesive systems.